Sounding out the state of Indonesian music - McGraw, Andrew Clay 1974-; Miller, Christopher J. 1969- (Southeast Asia Program Publications, 2022)
"An expansion on the 2018 Sounding Out the State of Indonesian Music conference that looks beyond the field's historical focus on gamelan and related traditional forms and reflects the broadening scope of Indonesian music studies"--
Keywords: Musikleben; Unterhaltungsmusik; Volksmusik; Indonesien; Music / Indonesia / History and criticism; Music / Social aspects / Indonesia; Musical groups / Indonesia; Performing arts / Indonesia; Konferenzschrift -- 29.03.2018-31.03.2018